Promotional Strategies using Instagram @baganjajanyuk to Boosting Customer in 2023 - Saputra, Muhammad Firdaus; Rasyid, Haryadi Arief Nuur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research provides a comprehensive exploration into how Bagan Jajan Yuk cafe strategically utilizes its Instagram account @baganjajanyuk for promotional endeavors, navigating a landscape marked by a burgeoning cafe industry and intense competition. Employing a qualitative descriptive approach, the study employs the AISAS model to analyze the effectiveness of this strategy.The findings illuminate Instagram's pivotal role as a potent tool in not only attracting but also engaging potential customers. The linchpin of this success lies in the consistent generation of captivating content. The sustained use of @baganjajanyuk on Instagram significantly amplifies interaction with potential patrons, fostering a heightened interest in experiencing the cafe's offerings and even eliciting recommendations to a broader audience.This research underscores the undeniable effectiveness of promotional strategies through Instagram, particularly when coupled with a sustained commitment to content consistency. This approach proves instrumental in not just reaching but also retaining customers, particularly within the younger demographic. The broad spectrum of engagement and its appeal to potential customers reiterates the paramount importance of leveraging Instagram as a pertinent and triumphant promotional platform.This study provides valuable insights into the contemporary business landscape, highlighting the pivotal role of social media, specifically Instagram, in crafting and executing successful promotional strategies. It offers a nuanced understanding of how online platforms can be harnessed to not only navigate but also excel in the dynamic and competitive modern market.